2019
DOI: 10.1016/j.isprsjprs.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently utilizing complex-valued PolSAR image data via a multi-task deep learning framework

Abstract: Convolutional neural networks (CNNs) have been widely used to improve the accuracy of polarimetric synthetic aperture radar (PolSAR) image classification. However, in most studies, the difference between PolSAR images and optical images is rarely considered. Most of the existing CNNs are not tailored for the task of PolSAR image classification, in which complex-valued PolSAR data have been simply equated to real-valued data to fit the optical image processing architectures and avoid complex-valued operations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Finally, the extracted features were classified by layers in the back of the network. In addition, there were some other deep networks used in the classification of PolSAR image, such as 3D-CNN combined with the conditional random field [30], CNN combined with graph [31], polarimatric convolutional network [32], Wishart deep stacking network S [33], Wishart autoencoder (Wishart-AE) [34], Wishart convolutional autoencoder (Wishart-CAE) [34], and the improved deep stacked network [35], [36]. Because some superpixel segmentation methods were proved to be effective in preserving spatial structure information of PolSAR images [37]- [39], the superpixel-based graph convolutional network was also proposed for PolSAR image classification [40].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the extracted features were classified by layers in the back of the network. In addition, there were some other deep networks used in the classification of PolSAR image, such as 3D-CNN combined with the conditional random field [30], CNN combined with graph [31], polarimatric convolutional network [32], Wishart deep stacking network S [33], Wishart autoencoder (Wishart-AE) [34], Wishart convolutional autoencoder (Wishart-CAE) [34], and the improved deep stacked network [35], [36]. Because some superpixel segmentation methods were proved to be effective in preserving spatial structure information of PolSAR images [37]- [39], the superpixel-based graph convolutional network was also proposed for PolSAR image classification [40].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid complex operations, Liu et al attempted to learn the feature of phase independently [27]. A two-stream architecture was proposed to extract features from amplitude and phase respectively with the aid of a multi-task feature fusion mechanism [28]. It is worth noting that PolSAR covariance matrix has been used as the input of CNNs in most studies [12,15,16,23,28], and the phase information is hidden between the input channels when each element of the upper triangle of PolSAR covariance matrix is regarded as a channel of the input.…”
Section: Introductionmentioning
confidence: 99%
“…A two-stream architecture was proposed to extract features from amplitude and phase respectively with the aid of a multi-task feature fusion mechanism [28]. It is worth noting that PolSAR covariance matrix has been used as the input of CNNs in most studies [12,15,16,23,28], and the phase information is hidden between the input channels when each element of the upper triangle of PolSAR covariance matrix is regarded as a channel of the input. Recent works have revealed that, with the aid of 3D operations, channel-wise correlations can be plugged in as an additional dimension of convolution kernels to solve the problem of feature mining on special data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…slow speed and lack of global information, fully convolutional networks [26] was introduced to achieve better full image classification [27], [28]. Some works studied new representations of PolSAR data, so as to improve the performance of CNN-based methods from the perspective of data [29]- [31]. Considering the particularity of PolSAR data, complex-valued CNN architectures have also been studied to some extent [32]- [34].…”
mentioning
confidence: 99%
“…This difficulty is partly reflected in the fact that architecture design requires considerable expertise of neural networks, which is lacking in PolSAR area. However, the author believes that with the efforts of researchers [31], [32], this will not be a stumbling block for future development. The author thinks that the main problem in the future research of CNNs-based PolSAR image classification methods is that the unsatisfactory performance of hand-crafted suboptimal architectures.…”
mentioning
confidence: 99%